2020
DOI: 10.1016/j.jaim.2018.02.138
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative role of antioxidant supplementation on sodium-arsenite induced adverse effects on the developing rat cerebellum

Abstract: Background Arsenic is an environmental contaminant of global concern. Consumption of ground water contaminated with inorganic arsenic (iAs) continues to be the major source of its exposure. The developing nervous system is especially vulnerable to environmental insults due to its higher rate of oxygen consumption and provision of weaker antioxidant (AOX) machinery. Objective Since oxidative stress has been reported as one of the major factors underlying iAs induced toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Thus, it seems that the improving effects of Cur on learning and memory are at least in part mediated by its antioxidant effects. Similar to our results, it was previously reported that Cur affected oxidative stress indicators in the cerebellum of the sodium-arsenite exposed rats during the development period (Kaushal et al , 2020). Also, the neuroprotective effect of Cur has been suggested to be related to its antioxidant and anti-inflammatory effects (Tsuda, 2018).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, it seems that the improving effects of Cur on learning and memory are at least in part mediated by its antioxidant effects. Similar to our results, it was previously reported that Cur affected oxidative stress indicators in the cerebellum of the sodium-arsenite exposed rats during the development period (Kaushal et al , 2020). Also, the neuroprotective effect of Cur has been suggested to be related to its antioxidant and anti-inflammatory effects (Tsuda, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, in recent studies, Cur in doses near the higher doses, including 100 and 150 mg/kg, which was used in the present study, improved the behavioral impairment in animal models induced by cadmium, diazepam, and D-galactose (Banji et al , 2014; Sevastre-Berghian and Făgărăsan, 2017; Namgyal et al , 2020). The protective effects of Cur on CNS functions, including learning and memory, have been suggested to be related to its protection against brain tissue oxidative damage (Banji et al , 2014; Sevastre-Berghian and Făgărăsan, 2017; Kaushal et al , 2020). In this study, Cur administration was dose-dependently accompanied by a decrease in both hippocampal and cortical MDA and an increase in thiol concentration and activities of CAT/SOD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fresh foods including spinach and broccoli and the turmeric in warm spiced golden milk provide dietary alpha-lipoic acid and curcumin that have been demonstrated to protect rat fetuses from central nervous system damage associated with arsenic that contaminates groundwater in some parts of the world. 15 Nourishing herbs can also be used when the fetus is not growing appropriately. There is some data to suggest that women diagnosed with upavistaka, or fetal growth restriction, can be treated with Shatavari (A. racemosus), Ashwagandha (Withania somnifera), and Bala (Sida cordifolia) to improve fetal growth.…”
Section: Ayurveda For Modern Obstetrics 593mentioning
confidence: 99%
“…In addition to desensitizing a pregnant woman’s nervous system, there is evolving basic science information that supports a nourishing diet as a means of ameliorating toxin-induced teratogenicity. Fresh foods including spinach and broccoli and the turmeric in warm spiced golden milk provide dietary alpha-lipoic acid and curcumin that have been demonstrated to protect rat fetuses from central nervous system damage associated with arsenic that contaminates groundwater in some parts of the world 15…”
Section: Application Of Ayurvedic Practices To Pregnancymentioning
confidence: 99%